A variação pronominal de segunda pessoa do singular em Coité do Nóia, AL - Silva, Suziane de Oliveira Porto (2019)
Based on the assumption that language is an important factor in the identification and demarcation of linguistic and social differences in the community, we aim, in this study, to draw the sociolinguistic profile of the speakers of the city of Coité do Nóia (LA) in relation to the pronominal second person singular tu/você/cê in the position of subject, with the purpose of analyzing how this variation occurs and which social and linguistic factors favor it. For the development of this study, we followed the theoretical-methodological assumptions of the Theory of Variation and Linguistic Change (LABOV, 2008) and to discuss existing relationships in communicative situations by observing the pronominal use or the forms of treatment in the speech community under study , we also consider the Theory of Power and Solidarity, according to Brown and Gilman (1960). In this way, we adopted the methodology of Variationist Sociolinguistics (LABOV, 2008; TARALLO, 2004; GUY; ZILLES, 2007), following some basic steps, namely definition of the dependent variable and independent variables; delimitation of the research sample; collection, transcription and quantification of data; description and interpretation of the results obtained. Our sample was stratified according to the social variables sex / gender and age group, with this, we selected 9 informants per cell, obtaining a total of 36 informants, generating, in this way, 18 dialogues. For the analysis of our data, we used the software GoldVarb X (SANKOFF, D .; TAGLIAMONTE, S., SMITH, E., 2005). After rounding and analyzing the data we obtained a total of 520 achievements, of which 57 of tu, 372 of você and 91 achievements of cê, representing a total of, respectively, 11%, 71% and 18%. As the statistical program used performs only binary rounds, we perform two distinct rounds, namely, you and you, and you and we. As a result, we had 11% of you and 89% of você/ cê in the first round, with four variables selected as statistically significant, namely relationship between age groups, pronominal parallelism, relationship between sexes and age group. Already in the second round we had 80% of you and 19% of cê, among the variables selected as statistically significant for the program we had the type of relationship between the interlocutors, the relationship between the sexes and the relations of symmetry and asymmetry.